Social Accountability in Health in Indonesia : An Overview of Legislation - Kusumaningrum, Santi; Siagian, Clara; Bennouna, Cyril; Laugen, Chris (World Bank, Washington, DC, 2019)
Social accountability (SA) refers to citizens' ability to ensure that their government fulfils its obligations and commitments and to hold the government responsible for violating or neglecting those duties. SA excludes voting for public officials, which is traditionally considered vertical accountability. SA may include citizen engagement with public officials, service providers, and policy makers, as well as with international development, civil society, and private sector actors. A commitment to social and gender inclusion usually underpins SA approaches, in recognition of the diversity of citizens' experiences, needs, and preferences, and of the state’s responsibility for all segments of the population.